STRATEGIES FOR ENHANCING EMPLOYE INNOVATION THRU ORGANIZATIONAL CULTURE STRENGTHENING PROGRAMS, TRANSFORMATIONAL LEADERSHIP AND EMPLOYE EMPOWERMENT - Abdul Khalim; Widodo Sunaryo; Yayan Hadiyat (Universitas KH. Abdul Chalim Mojokerto, 2026)
Employe innovation is a strategic factor in improving organizational performance and sustainability, particularly in educational institutions facing rapid changes. However, internal data from the Umar Usman Education Foundation shows that employe innovation levels are still relatively low. This study aims to analyze the influence of organizational culture and transformational leadership on employe innovation, both directly and indirectly thru employe empowerment as an intervening variable. This research uses a quantitative approach with a survey method. The study population includes all permanent employes of the Umar Usman Education Foundation at the staff level, totaling 153 people. Using a census technique, 116 respondents were obtained. Data was collected thru questionnaires that had been tested for validity and reliability, and then analyzed using path analysis with the help of SmartPLS version 4. The research results indicate that organizational culture and transformational leadership have a positive and significant influence on employe innovation. Employe empowerment also has a positive and significant influence on employe innovation. Additionally, transformational leadership has a positive and significant influence on employe empowerment, while organizational culture does not have a significant influence. Indirectly, transformational leadership significantly influences employe innovation thru empowerment, while organizational culture does not. These findings recommend strengthening organizational culture, transformational leadership, and employe empowerment.